Nanoindentation of Functionally Graded Polymer Nanocomposites: Assessment of the Strengthening Parameters through Experiments and Modeling - Nardi, Tommaso; Hammerquist, Chad; Nairn, John A.; Karimi, Ayat; Månson, Jan-Anders E.; Leterrier, Yves (Frontiers in Materials, 2015)
NNanoindentation tests were carried out on the surface of polymer nanocomposites exhibiting either graded or homogeneous distributions of Fe3O4@silica core-shell nanoparticles in a photocurable polymeric matrix. The results reveal a complex interplay between graded morphology, indentation depth and calculated modulus and hardness values, which was elucidated through numerical simulations. First, it was experimentally shown how for small (1 µm) indentations, large increases in modulus (up to +40%) and hardness (up to +93%) were obtained for graded composites with respect to their homogeneous counterparts, whereas at a larger indentation depth (20 µm) the modulus and hardness of the graded and homogeneous composites did not substantially differ from each other and from those of the pure polymer. Then, through a Material Point Method approach, experimental nanoindentation tests were successfully simulated, confirming the importance of the indentation depth and of the associated plastic zone as key factors for a more accurate design of graded polymer nanocomposites whose mechanical properties are able to fulfill the requirements encountered during operational life.